2001
DOI: 10.2214/ajr.176.4.1761059
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Anatomy of the Vertebral Venous System in the Thoracic Inlet

Abstract: he vertebral venous system in the thoracic inlet consists of the vertebral veins and perivertebral venous plexuses such as the anterior and posterior external plexuses and the internal plexus. Metastatic tumors can appear in locations that do not seem to be in the line of direct spread from their primary focus, which is called paradoxical metastasis. The vertebral venous system is well known as the pathway of paradoxical metastasis, as in bone metastases in patients with prostate cancer and breast cancer, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, there has been no detailed report describing the variations in the VV in the lower neck and there has been only a single report of one right VV, which was described as terminating at the lower portion of the BCV (Ibukuro et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there has been no detailed report describing the variations in the VV in the lower neck and there has been only a single report of one right VV, which was described as terminating at the lower portion of the BCV (Ibukuro et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The VV below the level of the sixth cervical vertebra has been reported as a round opacification adjacent to the VA that subsequently descends behind the internal jugular vein and ends in the BCV on enhanced CT (Ibukuro et al, 2001). In our study, besides a single VV, doubled VVs or VVs with unusual routes were observed.…”
Section: The Vertebral Vein Anatomy and The Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…These veins in turn are branched with connections to the spinal cord, basivertebral, occipital sinus, emissary, and posterior external plexuses. The external vertebral venous plexuses, best marked in the cervical region, consist of anterior and posterior plexuses which anastomose freely with each other: the vertebral, occipital, deep cervical, intercostal, lumbar, and pelvic veins [24]. The blood flow can reverse because there are no venous valves.…”
Section: Methodsmentioning
confidence: 99%
“…18 Moreover, a pathway between the vertebral and esophageal veins has been reported to play an important role in the genesis of DEVs in humans, making the varices plausible consequences of excessive blood flow. 19 In humans, selective angiography remains the gold standard for analysis of the anatomic and morphologic features of anomalous vascular connections. Conventional radiology, ecodoppler ultrasound examination, MDCT nonselective angiography, and flexible videoendoscopy were used in the dog described here.…”
mentioning
confidence: 99%